2023
DOI: 10.1007/s44192-023-00036-3
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the potential use of fluvoxamine for COVID-19 and long COVID

Abstract: Coronavirus disease 2019 (COVID-19) has presented a serious worldwide threat to public health since its emergence in late 2019. From a safety point of view, drug repurposing has received particular attention. Several clinical studies have demonstrated that the use of fluvoxamine, a selective serotonin reuptake inhibitor with potent sigma-1 receptor agonism, in the early-stage of infection might be associated with the prevention of clinical deterioration in individuals with SARS-CoV-2 infection, although severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 108 publications
0
12
1
Order By: Relevance
“…The transcription factor XBP1 in the ER plays a role in the reactivation of EBV [ 44 ]. Given the interaction of XBP1 and sigma-1 receptor in the ER, it is likely that sigma-1 receptor agonists (i.e., fluvoxamine), which may block EBV reactivation, would be potential therapeutic drugs to limit clinical deterioration after infection and long COVID symptoms [ 51 53 ]. Finally, SARS-CoV-2 can enter in the GI tract and cause dysbiosis of the gut microbiota in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcription factor XBP1 in the ER plays a role in the reactivation of EBV [ 44 ]. Given the interaction of XBP1 and sigma-1 receptor in the ER, it is likely that sigma-1 receptor agonists (i.e., fluvoxamine), which may block EBV reactivation, would be potential therapeutic drugs to limit clinical deterioration after infection and long COVID symptoms [ 51 53 ]. Finally, SARS-CoV-2 can enter in the GI tract and cause dysbiosis of the gut microbiota in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of the sigma-1 receptor on the regulation of XBP-1 in the ER [ 46 , 47 ], it is proposed that the potent sigma-1 receptor agonist fluvoxamine [a selective serotonin reuptake inhibitor (SSRI)] may be a potential therapeutic drug for long COVID (Fig. 2 ) [ 48 53 ]. A recent population-based retrospective study reported that the use of SSRIs with sigma-1 receptor agonism at baseline (at or prior to COVID-19 infection) was associated with a reduced risk of long COVID [ 54 ].…”
Section: Underlying Mechanisms Of Long Covidmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A systematic review of studies evaluating the use of fluvoxamine for COVID-19 and Long COVID suggested that baseline use of fluvoxamine may reduce the risk of Long COVID due to the drug's sigma 1 receptor agonist activity and the role of sigma 1 receptor activity in acute COVID-19 infection. 16 Observational analyses of human electronic health record (EHR) data did not find a significant difference in the relationship between moderate to high-affinity sigma 1 receptor agonist SSRIs (fluvoxamine, fluoxetine, escitalopram, and citalopram) versus non-high affinity SSRIs (sertraline and paroxetine) in their impact on Long COVID. 13 Identifying interventions that prevent Long COVID is crucial for clinical applications as well as our understanding of underlying biological mechanisms that cause Long COVID.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent review has emphasized the limited effectiveness of a low dose of fluvoxamine in preventing cytokine storms, as only a full dose of 200-300 mg daily can achieve this effect (Hashimoto, 2023). Other studies have highlighted conflicting results, especially for certain drugs such as tricyclic antidepressants and antipsychotics (Clelland et al, 2021;Min et al, 2022).…”
Section: Introductionmentioning
confidence: 99%